Improving The Use Of The Digital Economy In Regional Activities (A Case Study Of The Republic Of Karakalpakstan) (Eurasian Journal of History, Geography and Economics, 2024)
The digital economy is reshaping regional development by integrating advanced technologies into economic and social activities. This study explores the potential and current application of digital economy tools in the Republic of Karakalpakstan. Analyzing the challenges, opportunities, and policy interventions required for digital transformation, the research highlights key areas for improvement, focusing on infrastructure, education, and sector-specific digitalization strategies. The study concludes with recommendations aimed at fostering sustainable growth through the adoption of digital technologies